2017
DOI: 10.1007/s10040-017-1579-z
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater response to tidal fluctuations in wedge-shaped confined aquifers

Abstract: Most of the analytical solutions to describe tideinduced head fluctuations assume that the coastal aquifer has a constant thickness. These solutions have been applied in many practical problems ignoring possible changes in aquifer thickness, which may lead to wrong estimates of the hydraulic parameters. In this study, a new analytical solution to describe tide-induced head fluctuations in a wedge-shaped coastal aquifer is presented. The proposed model assumes that the aquifer thickness decreases with the dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Near the coast, a decreasing thickness (negative wedging parameter) produces a slope factor greater than 1. Similar results are reported by Cuello et al (2017) for an aquifer whose thickness decreases to zero. Conversely, an increasing thickness (positive wedging parameter) produces a slope factor smaller than 1 near the coast.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Near the coast, a decreasing thickness (negative wedging parameter) produces a slope factor greater than 1. Similar results are reported by Cuello et al (2017) for an aquifer whose thickness decreases to zero. Conversely, an increasing thickness (positive wedging parameter) produces a slope factor smaller than 1 near the coast.…”
Section: Resultssupporting
confidence: 91%
“…The solution is obtained by solving a boundary‐value problem combining the separation of variables and change of variables methods. This solution is a generalization of the solution obtained by Cuello et al (2017) for an aquifer whose thickness decreases with the distance to the coast. The effect of widening or thinning of the aquifer on the induced head fluctuations is analysed in terms of a wedging parameter.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Confined aquifer thickness has been shown to have a crucial role in the determination of groundwater signals. Hereby, Cuello et al [30] demonstrated that the wedging drastically increases the amplitude of the groundwater piezometric head inland. In 2007, Xia et al [26] presented an analytical solution of piezometric head inland, which incorporated several parameters in tidal methods: (i) subsea roof length extension, (ii) permeability of the outlet capping, (iii) outlet capping thickness, (iv) variable loading efficiency (LE), and (v) partial effects of the leakance within the offshore and inland sub-domains.…”
Section: Introductionmentioning
confidence: 97%